How Do Patient Satisfaction in Dental Polyclinic? - Patient Characteristics and Quality of Dental Health Services - Vitri Nurilawaty; Ngatemi; Dwi Priharti; Tedi Purnama; Ruth Lasma Milan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Excellent service is the demand of the community. Aspects of the quality of services provided will affectpatient satisfaction, where patients will compare between dental treatment at dental health service facilities.In improving the quality of service, the management of complaints from patients is needed.This studyaims to determinethe relationship between patient characteristics and the quality of dental health serviceson patient satisfaction. Method: this type of analytic observational study with cross sectional design. Theresearch was conducted on patients with dental polyclinic at the Health Center of Bukit Duri Village, TebetDistrict, South Jakarta. Data collection using a questionnaire.Data analysis using Chi-Square. Results:showed that the variable age had a p value of 0.691, gender with a p value of 0.013, a source of funding witha p value of 0.921 and the quality of dental health services with a p value of 0.001 on patient satisfaction.Conclusion: There is a significant relationship between gender and the quality of dental health services onpatient satisfaction at the dental clinic.